Adolescent Reproductive Health Education as an Effort to Increase Reproductive Health Knowledge and Marriage Readiness in Mancasan Kleben Village - Suryana, Rika; Rivaldi, Muhammad; Ninditya, Vika Ichsania; Ramadhany, Defy Rizky; Khatimah, Khusnul; Tasmara, Fikhri Astina; Amalia, Reski (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2024)
Adolescents in Yogyakarta encounter social disputes, klitih, cyberbullying,and reproductive health challenges,which have an impact on early marriage rates.Guidance from parents, communities, and the government is critical in minimizing juvenile criminality. To address issues such as unwanted pregnancies, unsafe abortions, and maternal mortality concerns, reproductive health education is critical. The Postgraduate Student Association of Universitas Gadjah Mada implemented the community engagement to educate teenagers in Mancasan Kleben Village, Pandowoharjo, Sleman Regency, Yogyakarta, about the importance of information on reproductive health in order to prevent early marriage and the transmission of sexual infections.The educational activity is conducted by giving lectures, pretest and post-test questionnaires, and discussion methods. The questionnaire’s results were analyzed using the t-test method. The result of the effect of education on reproductive health knowledge (76.25±7.621;80.61±3.047), and the impact of counseling on reproductive health knowledge is evident (12.80±2.28;21.27±1.71), and the effect on adolescent attitudes (58.20±4.38;65.73±7.51). Education about reproductive health and juvenile delinquency substantially impacts young people’s knowledge in Mancasan Kleben. The Postgraduate Student Association of Universitas Gadjah Mada activity was successfully implemented although the results were not statistically significant. Larger-scale service operations must be sustained to ensure that these outcomes give broader advantages.